C12B2Cu2F8H32S4O7 : A Versatile Redox Catalyst Isolated from Autoxidized Cu(CH3CN)4BF4 in Dimethylsulfoxide - Harald Gampp; Andreas D. Zuberbühler (CHIMIA)
The autoxidation product of Cu(CH3CN)4BF4 in dimethylsulfoxide (DMSO) could be isolated as solid Cu2(O)(DMSO)4(dioxane)(BF4)2, C12B2Cu2F8H32S4O7. The catalytic activity of this product on the oxidation of 2,6-dimethylphenol (1), benzoin (2), and 3,5-di-t-butylcatechol (3) by molecular oxygen was studied. As oxidation products poly(2,6-dimethyl-1,4-phenylene ether) (1a), benzil (2a), and 3,5-di-t-butyl-o-benzoquinone (3a) were isolated in good yields.